2014
DOI: 10.23846/ow2082
|View full text |Cite
|
Sign up to set email alerts
|

Does marginal cost pricing of electricity affect groundwater pumping behavior of farmers? Evidence from West Bengal, India

Abstract: The purpose of the evaluation was to quantify the impact of the recent policy change in West Bengal relating to the pricing of electricity from a flat rate tariff to metered tariff. The study attempted to assess its impact on the total number of hours pumped, especially in the summer season, and its distribution across use on the pump owner's own farm and sales to other farmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…Different states have implemented various policies for managing groundwater and electricity as water is a state subject and electricity is a concurrent subject. Several studies have looked at the effectiveness of indirect management of groundwater through electricity policies such as feeder segregation and rationing of electricity in Gujarat (Shah et al 2008), Karnataka and Punjab (Mukherji 2017); metering of electricity in West Bengal (Mukherji et al 2009;Meenakshi et al 2012). These studies concluded that political will is the main factor determining the success of these programs (Dubash et al, 2018).…”
Section: Evolution Of Solar Irrigation Policies In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…Different states have implemented various policies for managing groundwater and electricity as water is a state subject and electricity is a concurrent subject. Several studies have looked at the effectiveness of indirect management of groundwater through electricity policies such as feeder segregation and rationing of electricity in Gujarat (Shah et al 2008), Karnataka and Punjab (Mukherji 2017); metering of electricity in West Bengal (Mukherji et al 2009;Meenakshi et al 2012). These studies concluded that political will is the main factor determining the success of these programs (Dubash et al, 2018).…”
Section: Evolution Of Solar Irrigation Policies In Indiamentioning
confidence: 99%
“…More specifically, except in West Bengal (Meenakshi et al 2012), where there is some evidence that metering of agricultural electricity reduced groundwater pumping, in other states, it is not clear if electricity reforms affected groundwater use (Chindarkar & Grafton,2019). Meanwhile, irrigation Nuclear continues to consume up to 20-25% of India's total electricity.…”
Section: Evolution Of Solar Irrigation Policies In Indiamentioning
confidence: 99%
“…Where farmers do pay per m 3 of water, they use it more efficiently: in Spain, for example, groundwater irrigators apply less water than surface water irrigators and achieve higher returns for their output per unit of water applied (Garrido et al, 2005;Shah, 2014). In West Bengal, research found that electricity metering resulted in a significant reduction of hours pumped during the summer season, and that the resulting 33% decrease in water use did not affect the crop yield of summer paddy or cropping patterns (Meenakshi et al, 2013).…”
Section: What Is Agricultural Water Productivity?mentioning
confidence: 99%
“…Irrigation that depends on GW can become sustainable only when it involves community participation (Agoramoorthy and Hsu 2015). From previous studies (Mukherji et al 2010;Evans et al 2012;Meenakshi et al 2012), it is clear that there was a sudden increase in tube well installations from 2009, but no baseline data are available on the impact trends, especially for the last 4 years. Thus, no one knows the volume of GW storage trends in West Bengal.…”
Section: Introductionmentioning
confidence: 99%
“…District-wise monthly average rainfall data were gathered from the Indian Meteorological Department from 2002 to 2013. The number of tube wells was estimated from block-wise data, and past studies (e.g.,Mukherji et al 2010;Meenakshi et al 2012).…”
mentioning
confidence: 99%